A Thermodynamic Measure of Sustainability - Sciubba, Enrico (Frontiers in Sustainability, 2021)
A novel thermodynamic approach to the quantification of the “degree of sustainability” is proposed and discussed. The method includes a rigorous -and innovative- conversion procedure of the so-called externalities that leads to their expression in terms of the exergy of their equivalent primary resources consumption. Such a thermodynamic approach suggests a detailed re-evaluation of the concept of sustainability, in that, as pointed out by both Physicists and Economists in the past, the Second Law strictly negates the possibility for any open and evolving system to maintain itself in a “sustainable” state without availing itself of a continuous supply of low-entropy (i.e., high specific exergy) input. If a human society is modeled as an open system, its capacity to “grow sustainably” depends not only on how it uses non-renewable resources, but also on the rate at which it exploits the renewable ones. The necessary inclusion of different forms of energy- and material flows in such an analysis constitutes per se an argument in favor of a resource-based exergy metrics. While it is true that the thermodynamically oriented approach proposed here neglects all of the non-thermodynamic attributes of a “sustainable system” (in the Bruntland sense), it is also clear that it constitutes a rigorous basis on which different physically possible scenarios can be rigorously evaluated. Non-thermodynamic indicators can be still used at a “second level analysis” and maintain their usefulness to indicate which one of the “thermodynamically least unsustainable” scenarios is most convenient from an ethical or socio-economic perspective for the considered community or for the society as a whole. The proposed indicator is known as “Exergy Footprint”, and the advantages of its systematic application to the identification of “sustainable growth paths” is discussed in the Conclusions.